Utility of real‐time three‐dimensional echocardiography in improved assessment of a mitral valve papillary fibroelastoma - Suresh, Rahul (Clin Case Rep, 2017)
Primary cardiac tumors are exceedingly rare. They are usually first identified by transthoracic echocardiography. However, transesophageal echocardiography (TEE), with the aid of real‐time three‐dimensional (3D) imaging, can provide additional important mass characteristics. We present a case that demonstrates the usefulness of 3D TEE in characterizing a papillary fibroelastoma.